У буквенное выражение.
7x - 5 - 4(2x – 9)
5(x - 3) - (6x - 11)=
x - 7 - 3(2x - 8) =
6(2x + 3) – 4(7x – 20) =

pierrotsadclown pierrotsadclown    3   16.04.2020 17:25    0

Ответы
Котеика1космос Котеика1космос  13.10.2020 09:31
7х - 5 - 8х - 36= -1х - 41
5х-15-6х-11= -1х-26
х-7-6х-24= -5-31
12х+18-28х-80=-16-62
ПОКАЗАТЬ ОТВЕТЫ
ПоляКрасавица1 ПоляКрасавица1  13.10.2020 09:31

-9x + 93

Пошаговое объяснение:

6(2x + 3) – 4(7x – 20) = 12x + 13 - 21x + 80 = -9x + 93

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика